The Instant Food Revolution: Exploring Modern Consumer Buying Patterns - Mathew, Anu P.; Mathew, Dinoy (International Socioeconomic Review, 2024)
Aims: This research explores the evolving consumer purchasing behavior towards instant food products, focusing on the Central Kerala region. The study investigates the impact of demographic factors on consumer perceptions, the influence of instant food products, and the role of gender, income, and occupation in shaping purchasing decisions. Additionally, it examines consumer awareness of potential health risks associated with instant food consumption. Methodology: Employing a descriptive and analytical research design, data were gathered from 240 respondents in Central Kerala, using a structured questionnaire and analyzed through statistical tools like SPSS, MS Excel, and various inferential tests, including the Kruskal-Wallis H Test, Mann-Whitney U Test, and Pearson Correlation. Results: Findings reveal that convenience, taste, and time-saving benefits are primary drivers of instant food consumption, especially among urban residents and working professionals. Advertising, peer recommendations, and personal preferences significantly influence purchasing behavior. However, a notable concern for health risks associated with processed foods, such as obesity, diabetes, and heart disease, is emerging among consumers. This health consciousness is reshaping consumer choices, prompting a demand for healthier instant food options. Implications: The study concludes that while convenience and taste remain pivotal, there is a clear shift towards health-conscious decision-making among consumers. This presents a critical opportunity for businesses and policymakers to offer healthier alternatives and promote nutritional awareness.